2020
DOI: 10.1021/acs.jpcb.0c01414
|View full text |Cite
|
Sign up to set email alerts
|

Ergodicity Breaking in Thermal Biological Electron Transfer? Cytochrome C Revisited II

Abstract: It was recently suggested that cytochrome c operates in an ergodicity-breaking regime characterized by unusually large energy gap thermal fluctuations and associated reorganization free energies for heme oxidation of up to 3.0 eV. The large fluctuations were reported to lower activation free energy for oxidation of the heme cofactor by almost a factor of 2 compared to the case where ergodicity is maintained. Our group has recently investigated this claim computationally at several levels of theory and found no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Consequently, λ rxn in Omc- E, S, and Z, respectively, is nearly the same as λ st : 0.481 to 0.871, 0.429 to 0.983, and 0.556 to 0.892 eV. The observation that λ st ≈ λ i var ≈ λ f var implies that ergodicity-breaking is not observed as a mechanism for lowering the activation barrier to electron transfer in all three “nanowires” on the timescale of the current dynamical simulations. Standard Marcus theory applies in this case. All three “nanowires” have very similar outer-sphere reorganization energies, even though the protein matrices and heme solvent accessibilities are very different.…”
Section: Resultsmentioning
confidence: 72%
“…Consequently, λ rxn in Omc- E, S, and Z, respectively, is nearly the same as λ st : 0.481 to 0.871, 0.429 to 0.983, and 0.556 to 0.892 eV. The observation that λ st ≈ λ i var ≈ λ f var implies that ergodicity-breaking is not observed as a mechanism for lowering the activation barrier to electron transfer in all three “nanowires” on the timescale of the current dynamical simulations. Standard Marcus theory applies in this case. All three “nanowires” have very similar outer-sphere reorganization energies, even though the protein matrices and heme solvent accessibilities are very different.…”
Section: Resultsmentioning
confidence: 72%
“…The field vector from each MD snapshot (sample) was rotated to the coordinate frame used in the ZINDO calculations, following the procedure described in ref. 91, and then used to construct the PMM Hamiltonian, eqn (7). The field strength and orientation found in azurin are consistent with a recent study of Bim and Alexandrova, 92 who studied local field in a group of more than 30 cupredoxins and observed that the field vectors are typically pointing to the opposite direction than and vectors.…”
Section: Resultsmentioning
confidence: 99%
“…The polarizability evaluated by ZINDO on QC-5 has magnitude ∼4 Å 3 , which is by one order lower value than polarizabilities of redox sites in cytochromes. 91 This indicates that the transition dipole moments μ ij are small and so are their scalar products with the intrinsic field E . As these products determine the off-diagonal Hamiltonian elements (eqn (7)), the resulting Hamiltonian is practically quasi-diagonal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…94,95 Polarizability of the heme active site may further lower the reorganization energy, as proposed for cytochrome c on the basis of semi-empirical quantum chemistry (ZINDO/S) calculations, 96 although this point has been debated. [97][98][99] However, density functional theory calculations for the hemes in the cytochrome filaments found only <0.04 eV shifts in the reorganization energy when relaxing vacuum-optimized electron densities in the presence of the perturbing protein/water environment (Tables S4-S6. 74 Polarizability corrections are not expected to vary widely between proteins, as evidenced by recommendations of system-independent scaling factors.…”
Section: Reorganization Energymentioning
confidence: 99%